Side Information Generation for Distributed Video Coding Using Spatiotemporal Joint Bilinear Upsampling. (14th April 2014) - Liu, Wenhui; Vijayanagar, Krishna Rao; Kim, Joohee
Abstract : Distributed video coding presents a viable solution for power-constrained multimedia communication. However, its relatively low coding efficiency compared to the conventional video coding schemes remains a challenging issue. The rate-distortion performance of distributed video coding is highly dependent on the quality of side information generated at the decoder and various techniques have been proposed to improve the side information quality in block-based and frame-based distributed video coding architectures. In this paper, a robust spatiotemporal joint bilateral upsampling based side information generation method is proposed. The proposed side information generation method is based on a block-based low-complexity distributed video coding architecture with adaptive block coding mode classification. A partially reconstructed Wyner-Ziv (WZ) frame with skip and key blocks is downsampled and spatiotemporal error concealment and joint bilateral upsampling are used to generate the side information. Simulation results show that the proposed method improves the quality of side information significantly while keeping low computational complexity.